2017
DOI: 10.1089/jamp.2016.1300
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Antibiotic Therapy for the Treatment of Upper Respiratory Tract Infections

Abstract: Upper respiratory tract infections (URTIs), primarily acute rhinopharyngitis, tonsillitis, adenoiditis, and rhinosinusitis (RS), are major causes of morbidity in both children and adults of any age. In addition to the frequent occurrence of related medical problems and the associated socioeconomic costs, URTIs have a significant impact on the quality of life of patients and their families, and have placed an escalating financial burden on the global healthcare system. Most URTIs are caused by viruses and requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
3
0
3
Order By: Relevance
“…Gentamicin, amikacin, tobramycin and colistin/polymyxin B all have good effects on the three diseases mentioned previously. However, some other drugs, such as ceftazidime, have no effect on NCFB, and vancomycin only has an effect on VAP (Esposito et al, 2017;Mogayzel et al, 2013;Restrepo et al, 2015). Of note, 219 (11.1%) respondents reported that antibiotics as an atomised drug were used in their ICU, whereas bronchodilation was the most commonly used aerosol therapy.…”
Section: The Specific Operation and Optimal Delivery Techniquesmentioning
confidence: 99%
“…Gentamicin, amikacin, tobramycin and colistin/polymyxin B all have good effects on the three diseases mentioned previously. However, some other drugs, such as ceftazidime, have no effect on NCFB, and vancomycin only has an effect on VAP (Esposito et al, 2017;Mogayzel et al, 2013;Restrepo et al, 2015). Of note, 219 (11.1%) respondents reported that antibiotics as an atomised drug were used in their ICU, whereas bronchodilation was the most commonly used aerosol therapy.…”
Section: The Specific Operation and Optimal Delivery Techniquesmentioning
confidence: 99%
“…Чаще всего при вирусных инфекциях поражаются верхние дыхательные пути, и наибольшее распространение, помимо повышения температуры, имеют такие симптомы, как насморк, кашель, боль в ухе или в горле [12].…”
Section: бронхопульмонология и лорunclassified
“…Именно с вирусными тонзиллитами мы стал-киваемся почти в 80% случаев [16]. Лечение такого тон-зиллита подразумевает симптоматические средства -купирование болевого синдрома при его наличии, мест-нодействующие антисептики, а также снижение высокой температуры, если она есть [2]. [17][18][19].…”
Section: в чем проблема?unclassified
“…Рассматриваются также альтернативные 5-дневные курсы лечения для цефуроксима аксетила и азитромицина и даже ведутся работы по возможности назначения антибиотика в виде спреев и ингаляций [2].…”
Section: лечение отunclassified